The effect of STEAM education with tales on problem solving and creativity skills - Erol, Ahmet; Erol, Mustafa; Basaran, Mustafa (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2023)
The study aims at examining the effects of Engineering Design Process Based STEAM activities applied with tales on the creativity and problem-solving skills of 6-6.5 year-old students. The research was carried out with a pre-test, post-test, and quasi-experimental design with the control group. The research participants consisted of students studying in a public school located in the Gaziosmanpasa District of Istanbul Province. The research was carried out with the participation of 68 students. The research data were obtained through early childhood creativity scale (ECCS) and problem-solving skills scale (PSSS). The data were analyzed by t-test and pearson correlation analysis for dependent and independent samples. According to the results obtained in the research, the Engineering Design Process Based STEAM (EDP-STEAM) activities applied with tales improved the students' creativity and problem-solving skills. The findings point to the positive effects of EDP-based STEAM education conducted with tales on students' problem solving and creativity skills. In this aspect, the study provides recommendations for future research and educators.
Keywords: Early childhood; STEAM education; tales; creativity; problem solving; CHILDHOOD; ARTS; Education & Educational Research